PARENTS’ PERSPECTIVE OF CHILDREN’S EDUCATION IN HANDIL SOHOR VILLAGE, EAST KOTAWARINGIN REGENCY (International Conference on Social and Islamic Studies, 2021)
The results showed that: 1. Parents’ perspective on children’s education include: a) understanding, most of the subjects said that education for children is important. The children’s education should be continued to a higher level if the family has a good economy, b) The attitude, the attitude of parents’ care to their children’s education is quite good, this can be proven from the existence of children’s educational facilities which are always attempted by their parents, c) Responses, parents’ responses to the children’s education are generally good because parents often give their children advice regarding how important education is for the future. 2. Parents’ duty and responsibility for children’s education is sufficient. It can be seen from the parents who have not given faith development for their children. Few parents do moral education. In the intellectual development of children, it seems that the parents are still not optimal. It is proven by the children who dropped out of school. Whereas in social development, parents only give their advice to their children. 3. Factors that influence parents on children’s education are a) Lack of parental knowledge and understanding of education, b) Lack of parental awareness of the importance of education in a family, c) Economic pressure for family needs.